Effect of a Multidimensional Fall Prevention Program on Incidence of Falling and Quality of Life among Elderly - Tahereh Najafi Ghezeljeh; Zohreh Parsa Yekta; Abbas Mehran; Mehdi Jafari Oori (Tehran University of Medical Sciences, 2014)
Background & Aim: Falling is common among elderly due to changes in sensory-motor function. Falling causes physical, emotional and financial problems and decreases the quality of life in elderly. Since the causes of falling are multifactorial, multi-dimensional approaches should be considered to prevent it. This study aimed to investigate the effect of a multidimensional fall prevention program on the incidence of falling and quality of life among old people living in nursing homes.   Methods & Materials: This before-after quasi-experimental study was conducted on 60 old people living in nursing homes who met the inclusion criteria. Multidimensional fall prevention program was focused on: 1- exercise (stretching, balance, and strength) 2-training classes for caregivers and elderly and 3-environmental modification. Data were collected before and six months after the intervention using demographic and illness form, fall frequency form and the LEIPAD questionnaire. Collected data were analyzed using the paired t-test, one-way ANOVA, Mann-Whitney and Wilcoxon tests in the SPSS-16 .    Results: Before and six months after the intervention, the mean frequencies of falling were 2.00 (±0.70) and 0.20 (±0.55), respectively. The mean scores of quality of life before and six months after the intervention w ere 56.48 (±10.45) and 77.43 (±10.45), respectively. Results indicated that there were statistically significant difference between the study participants before and six months after the intervention regarding falling frequency (P<0.001) and quality of life score (P<0.001).   Conclusion: The multi-dimensional fall prevention program decreased the fall frequency and increased quality of life of participants. Health care providers, particularly nurses can use the prevention program to diminish falling incidence among elderly and improve their quality of life.